The Role of Inflammatory Cytokines, the RANKL/OPG Axis, and the Immunoskeletal Interface in Physiological Bone Turnover and Osteoporosis. (3rd February 2013) - Weitzmann, M. Neale
Abstract : Although it has long been recognized that inflammation, a consequence of immune-driven processes, significantly impacts bone turnover, the degree of centralization of skeletal and immune functions has begun to be dissected only recently. It is now recognized that formation of osteoclasts, the bone resorbing cells of the body, is centered on the key osteoclastogenic cytokine, receptor activator of NF- κ B ligand (RANKL). Although numerous inflammatory cytokines are now recognized to promote osteoclast formation and skeletal degradation, with just a few exceptions, RANKL is now considered to be the final downstream effector cytokine that drives osteoclastogenesis and regulates osteoclastic bone resorption. The biological activity of RANKL is moderated by its physiological decoy receptor, osteoprotegerin (OPG). New discoveries concerning the sources and regulation of RANKL and OPG in physiological bone turnover as well as under pathological (osteoporotic) conditions continue to be made, opening a window to the complex regulatory processes that control skeletal integrity and the depth of integration of the skeleton within the immune response. This paper will examine the interconnection between bone turnover and the immune system and the implications thereof for physiological and pathological bone turnover.